(NwEK NYNE[NIJ I WEK MINUW[IJ (B:s (NSTATXI O MUZYKE (B/s - (NnESTXEW(B, (NiZRAILX wLADIMIROWI^(B,s; (NoRDVONIKIDZE(B, (Ng(B. (N{(B.,s ((NmOSKWA (B:s (NsOWETSKIJ KOMPOZITOR(B,s, 1986)
(No PROBLEMAH ZARUBEVNOGO MUZYKALXNOGO ISKUSSTWA (B20 (NWEKA(B.s
(NbIBLIOGR(B. (NW PODSTRO^NOM PRIME^(B. - (NbIBLIOGR(B.: (NS(B. 374-381s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpROKOF(B')QÃ(NW s(B. (Ns(B.s)E; (NbARTOK b(B.s; (NeJSLER g(B.s; (N{OSTAKOWI^ d(B. (Nd(B.s; (NmUZIKAs -- )Qæ(NSTORÆQ MUZIKIs)E; (NROS)QÆJSXKA MUZIKAs)E; (NZARUB)QÆVNA MUZIKAs)E; (NKOMPOZITORIs; (NOPERNA TWOR^)QÆSTXs)E; (NBALETNA TWOR^)QÆSTXs)E